Evaluation of Depression and Cognitive Status in Geriatric Patients Undergoing Orthopedic Surgery - Yildirim Safak, E; Savci, A; Kuyubaşi, S. N (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: Cognitive disorders are common in geriatric surgical patients We conducted a study to evaluate depression and cognitive behavior in geriatric patients undergoing orthopedic surgery. MATERIAL AND METHODS: This descriptive cross-sectional study was conducted at a university hospital in Turkey, involving 262 elderly patients who underwent orthopedic surgeries. Data were collected using The Patient Information Form, Standardized Mini-Mental Test, and Geriatric Depression Scale. RESULTS: The mean score of the Standardized Mini-Mental Test scale of the patients after surgery was 17.97±4.99, mean score of the Geriatric Depression Scale was 6.20±2.78. The study revealed that 85.1% (n=223) of the participants had cognitive impairment and 69.1% (n=181) depressive symptoms. Additionally, cognitive impairment and depressive symptoms increased as age, pain scores, and length of hospital stay increased. Our research also showed that individuals with a history of falls, visual/hearing impairment, malnutrition, use of assistive devices, dependence on others for daily activities, non-educated or single, individuals are more likely to experience geriatric depression and have a higher of cognitive impairment. Additionally, patients who have had hip arthroplasty, have low hemoglobin levels, or have high ASA scores are more prone to cognitive impairment. Cognitive impairment was more common in patients with higher depression scores. CONCLUSIONS: Considering these findings, it is crucial to identify the cognitive disorders and depressive symptoms during their initial hospitalization to prevent or treat them in geriatric patients. Regular monitoring of geriatric patients in orthopedic clinics for symptoms of cognitive status and depression is recommended, and caregivers should be made aware of this issue. KEY WORDS: geriatric patients, orthopedic procedures, cognitive status, depression.
Keywords: Cross-Sectional Studies; senioři nad 80 let; Length of Stay; Humans; geriatrické hodnocení; ortopedické výkony; Turecko; Cognitive Dysfunction; Aged, 80 and over; mužské pohlaví; Turkey; Depression; průřezové studie; kognitivní dysfunkce; Geriatric Assessment; délka pobytu; ženské pohlaví; lidé; deprese; Orthopedic Procedures; Aged; senioři; Male; Female